Combined Effects of Block-Based Programming and Physical Computing on Primary Students' Computational Thinking Skills - Kastner-Hauler, Oliver; Tengler, Karin; Sabitzer, Barbara; Lavicza, Zsolt (Frontiers in Psychology, 2022)
Basic Digital Education (BDE) is already planned to be integrated with the forthcoming curriculum for Austrian primary schools (6 to 10 years) as it was already implemented for lower secondary schools (10 to 14 years) in 2018. BDE includes most essential and novel developments of Computational Thinking (CT), fundamentally responsible for nurturing students’ problem-solving skills. Thus, evaluating teaching materials, scaffolding guidelines, and assessments is becoming increasingly important for the successful implementation of CT in Austrian classrooms. This study is a part of a longitudinal multi-cycle educational design research project aiming to explore how to foster CT and to raise the awareness, importance, and confidence of teachers and students in applying CT for everyday uses. Our paper focuses on a sub-study in which teaching units for grade 3 and 4 students (8 to 10 years) were designed combining an Open Educational Resource (OER) textbook and Physical Computing with the micro:bit device. The designed learning environment consists of three units and was implemented in two classes over a three-week period. The two classes were further split into two groups each, to ensure better support during implementation. The class teachers received upfront teacher training and conducted pre- and post-test assessments with the students. The resulting data was then analyzed to gain insights into the effects on CT skills of the young learners. Results showed that combining block-based programming and physical computing devices could become a promising approach to promote computational thinking skills in lower school grades. Furthermore, the observed direction of the designed units supports low-barrier access to increase the desired uses of CT in classrooms.